The Effect of Technological Infrastructure on Managerial Innovation: The Mediating Role of Knowledge Management Processes - Hassan Smadi , Ahmad; Ziad AL Zoubi, Jumana; Masa’deh, Ra’ed (Jordan Journal of Business Administration, 2025)
This study aimed to identify the impact of the technological infrastructure on managerial innovation in the Jordanian Ministry of Interior with evaluating the mediating role of knowledge management processes (knowledge acquisition, knowledge storage, knowledge transfer, and knowledge application). The study adopted the descriptive analytical causal approach to achieve its objectives; the study used the simple random sample method by distributing an electronic questionnaire consisting of (32) items that measure the study variables. The study population was represented by all workers in the centers of the governorates of the Jordanian Ministry of Interior, which numbered (515) employees, while the study sample consisted of (327) employees. The results showed that there is a positive impact of the technological infrastructure and knowledge management processes on managerial innovation, where the coefficient of determination (R2) indicates that the technological infrastructure with knowledge management processes as an intermediate role explains (77.4%) of the variation in managerial innovation as a dependent variable. The study recommended based on the results developing strategies to employ the technological infrastructure and use its components to improve managerial innovation. Also, the study recommended the necessity of activating the official means of communication and exploiting the available knowledge resources to explore creative ideas and apply them through the administrative units in the governorates of the Jordanian Ministry of Interior.